PERAN PENYULUH BERBASIS MASYARAKAT DALAM MEMPERTAHANKAN HUTAN JANDA (KAOMBO OHUSII) DI KABUPATEN BUTON SULAWESI TENGGARA - Najib Husain; Basrudin; Abdul jalil; Adrian Tawai; Dewi Anggraini (Journal Publicuho, 2024)
This study aims to explore the management practices of Widow Forest (Kaombo Ohusii) in Buton Regency through the lens of local wisdom and development communication, by revealing the social, cultural, and environmental dynamics involved in forest management. This study uses a variety of data collection methods. Participant observation allows researchers to be directly involved in Widow Forest management activities, observe the practices carried out, and interact with local communities and other parties involved in natural resource management. In-depth interviews will be conducted with widows, poor women, community leaders, government officials, and non-governmental organizations involved in the management of Widow Forest. The results of the study show that community-based extension by traditional officials in Takimpo Village in the management of Widow Forest (Kaombo Ohusii) is an example of effective local participation in sustainable natural resource management. The involvement of this traditional institution also shows the importance of integrating local values in development, ensuring that decisions taken are in accordance with community expectations, and supporting environmental conservation and community empowerment.